The Malay enclave of Kampong Bharu as a living tradition: a place of uncertainty - Ujang, Norsidah; Abdul Aziz, Faziawati (e-International Publishing House, 2016)
In the case of Asian cities, poor redevelopment process has often resulted in the loss of historic urban fabric. Kampong Bharu is a traditional Malay settlement in the heart of the Kuala Lumpur city, holds a unique case of a struggle to preserve its local identity. This paper reviews the scenario regarding the enclave in light of the current redevelopment proposal. Reviews of literature and analysis of recent reports indicated that the future of the enclave is in the state of uncertainty. People oriented planning based upon a deep understanding of culture and tradition could bring about a natural approach towards a definitive redevelopment initiatives.© 2016. The Authors. Published for AMER ABRA by e-International Publishing House, Ltd., UK. Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia.